2010
DOI: 10.1377/hlthaff.2010.0146
|View full text |Cite
|
Sign up to set email alerts
|

Low Costs Of Defensive Medicine, Small Savings From Tort Reform

Abstract: In this paper we present the costs of defensive medicine in thirty-five clinical specialties to determine whether malpractice liability reforms would greatly reduce health care costs. Defensive medicine includes tests and procedures ordered by physicians principally to reduce perceived threats of medical malpractice liability. The practice is commonly assumed to increase health care costs. The results of studies of the costs of defensive medicine have been inconsistent. We found that estimated savings resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…0 8 A study by Sloan and Shadle that covered more conditions and a longer span of years also produced insignificant results.1 09 A recent study's findings are summed up by its title: there are "low costs" associated with defensive medicine, and "small savings from tort reform." 110 Other studies have found stronger evidence of defensive medicine. One recent study found that health care spending was 3-4 percent lower in states that had adopted tort reform,' and another review put the cost of defensive medicine at $45.6 billion, while acknowledging the poor quality of the evidence supporting this figure.112…”
Section: Cost Of the Liability Systemmentioning
confidence: 97%
“…0 8 A study by Sloan and Shadle that covered more conditions and a longer span of years also produced insignificant results.1 09 A recent study's findings are summed up by its title: there are "low costs" associated with defensive medicine, and "small savings from tort reform." 110 Other studies have found stronger evidence of defensive medicine. One recent study found that health care spending was 3-4 percent lower in states that had adopted tort reform,' and another review put the cost of defensive medicine at $45.6 billion, while acknowledging the poor quality of the evidence supporting this figure.112…”
Section: Cost Of the Liability Systemmentioning
confidence: 97%
“…23 Researchers produced similar estimates of the impact of tort reform derived using different data sources and time periods. The estimated range of savings derived from a 10 percent decrease in malpractice premiums is 0.13 percent to 1.2 percent of total healthcare expenditures [145,148,149].…”
Section: Medical Malpractice Reformmentioning
confidence: 99%
“…Kessler and McClellan (1996) found that laws restricting malpractice damages were associated with decreased spending in heart condition patients, but Currie and MacLeod (2008) found they resulted in increased use of C-section procedures in births. Other authors generally found small effects or no statistically significant evidence for defensive medicine (Dubay et al, 1999(Dubay et al, , 2001Baicker et al, 2007;Kim, 2007;Carrier et al, 2010;Thomas et al, 2010). Lakdawalla and Seabury (2012) found defensive medicine had moderate effects on spending growth, but argued these costs were justified by reduced mortality 3 .…”
Section: Introductionmentioning
confidence: 99%